1603 A Google Trends Analysis of Interest in Ear, Nose and Throat Surgery During The COVID-19 Pandemic. (12th October 2021) - Williams, C Y K; Ferreira, A F; Townson, A T; Pace, A
Abstract: Aim: The COVID-19 pandemic has had wide-ranging effects on healthcare, society and everyday life. As the public's health priorities shift, we sought to investigate the resulting impact of COVID-19 on global interest in Ear, Nose and Throat (ENT) surgery. Method: We used Google Trends to examine worldwide search interest in the following core ENT operations following the onset of the COVID-19 pandemic: Tonsillectomy, Adenoidectomy, Thyroidectomy, Rhinoplasty, Septoplasty, Functional Endoscopic Sinus Surgery, Mastoidectomy, and Tympanoplasty. Bayesian structural time-series models were used to generate counterfactual time series, and relative differences between observed and expected search interest were calculated. Causal effects were subsequently determined, along with 95% CIs and posterior probabilities. R version 4.0.3 was used for analyses. Results: Search interest in all measured ENT procedures was significantly reduced at the onset of the COVID-19 pandemic. Interest in Rhinoplasty recovered after 8 weeks and continued to rise to a peak of 27% greater than expected, with a cumulative Relative effect of + 11% [95% CI: 3.9%, 20%]. In contrast, significantly reduced search interest was observed for all other procedures analysed (Relative effect, range: -16% to -36%, all p values < 0.05). Conclusions: Our findings suggest divergent changes in public interest in common ENT procedures. While all other ENT operations investigated were less frequently searched following the pandemic onset, interest in Rhinoplasty at times increased to over 25% greater than expected. This could represent a shift in patient attitudes to disorders of the Ear, Nose and Throat and warrants further investigation at the individual-level.